2004
DOI: 10.1523/jneurosci.1939-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Signs of Nicotine Withdrawal in Mice Null for the β4 Nicotinic Acetylcholine Receptor Subunit

Abstract: Withdrawal from chronic exposure to nicotine, the main addictive component of tobacco, produces distinctive symptoms in humans. The appearance of these symptoms is a major deterrent when people try to quit smoking. To study which type of nicotine receptor is relevant for the onset of the withdrawal syndrome, we used a mouse model of nicotine withdrawal. Wild-type mice and mice null for the ␤4 (␤4Ϫ/Ϫ) or the ␤2 (␤2Ϫ/Ϫ) nicotinic acetylcholine receptor subunits were implanted with osmotic minipumps delivering 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
233
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(253 citation statements)
references
References 31 publications
18
233
1
1
Order By: Relevance
“…Genetic knockout studies have resolved this issue. β2 KO mice showed somatic symptoms, such as excessive rearing, body shakes or over-grooming, during withdrawal precipitated by the broad-spectrum nAChR antagonist mecamylamine (Besson et al, 2006;Salas, Pieri, & De Biasi, 2004). In contrast, β4 KO mice exhibited significantly reduced somatic symptoms during mecamylamine-precipitated withdrawal (Salas et al, 2004), suggesting that somatic symptoms of nicotine withdrawal involve β4-containing but not β2-containing nAChRs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genetic knockout studies have resolved this issue. β2 KO mice showed somatic symptoms, such as excessive rearing, body shakes or over-grooming, during withdrawal precipitated by the broad-spectrum nAChR antagonist mecamylamine (Besson et al, 2006;Salas, Pieri, & De Biasi, 2004). In contrast, β4 KO mice exhibited significantly reduced somatic symptoms during mecamylamine-precipitated withdrawal (Salas et al, 2004), suggesting that somatic symptoms of nicotine withdrawal involve β4-containing but not β2-containing nAChRs.…”
Section: Discussionmentioning
confidence: 95%
“…β2 KO mice showed somatic symptoms, such as excessive rearing, body shakes or over-grooming, during withdrawal precipitated by the broad-spectrum nAChR antagonist mecamylamine (Besson et al, 2006;Salas, Pieri, & De Biasi, 2004). In contrast, β4 KO mice exhibited significantly reduced somatic symptoms during mecamylamine-precipitated withdrawal (Salas et al, 2004), suggesting that somatic symptoms of nicotine withdrawal involve β4-containing but not β2-containing nAChRs. Overall, these investigations together with the current findings demonstrate that β2-containing nAChRs are involved in the effects of nicotine on learning, reward/reinforcement, and cognitive withdrawal symptoms, but not somatic nicotine withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the somatic symptoms of nicotine withdrawal are present in both β2 KO and WT mice, suggesting that the somatic symptoms of nicotine withdrawal are mediated by other nAChR subunits [7,77,146]. Research with other nAChR subunit KO mice has demonstrated that the β4 [146], α5 [77], and α7 nAChR subunits [148] likely mediate the somatic symptoms of withdrawal. Thus, these studies provide evidence that the various symptoms of nicotine withdrawal are mediated by different nAChR subunits.…”
Section: The β2 Nachr Subunitmentioning
confidence: 99%
“…Finally, β4 KO mice have been tested for several phenotypes and show some similarity to α3 and α5 KO mice. For example, β4 KO mice exhibit reduced sensitivity to the hypolocomotor effects of nicotine, have increased resistance to nicotine-induced seizures, and show reduced somatic signs during nAChR antagonist-precipitated withdrawal when compared to WT mice [147,146]. Furthermore, the core body temperature of β4 KO mice is lower than WT mice, and the effects of nicotine on body temperature are reduced in the KO mice [143].…”
Section: Additional Nachr Subunitsmentioning
confidence: 99%
“…[7][8][9][10][11] Further, studies in knockout mice show that the β4 nAChR subunit is necessary for nicotine withdrawal because withdrawal is greatly diminished in β4 null mice, but not in β2 null mice. 12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence. [14][15][16][17] Consistent with the genetic and knockout studies, a transgenic mouse model overexpressing the human CHRNA5/Α3/Β4 genomic cluster showed significantly increased β4* nAChR binding in the medial habenula and increased acquisition of nicotine self-administration.…”
Section: Introductionmentioning
confidence: 99%